Penggunaan Podcast sebagai Media Alternatif dalam Pembelajaran Bahasa Arab - Syamlan, Atika Chairul; Mufidah, Zuhrotul (Global Action and Education for Society, 2024)
The use of alternative media in learning Arabic is becoming increasingly relevant in the digital age. One of the media that has great potential is the podcast. This article discusses the effectiveness of podcasts as a tool for learning Arabic, covering methods, results, and interpretation of the research carried out. The study involved 50 high school students divided into experimental groups and control groups. Research methods include pre-test and post-test to measure improvement in Arabic language skills as well as interviews and questionnaires to dig students' experiences. Research results show that podcasts can improve students' understanding of Arabic material, especially in the aspect of listening and speaking. The discussion also covered challenges, such as device and internet access constraints, as well as strategies to maximize the use of podcasts in learning, including combinations with face-to-face sessions and the provision of additional resources. With the right approach, podcasts can be an effective tool in learning Arabic.